Multimedia Signals and Systems Basic and Advanced Algorithms for Signal Processing - Stanković, Srdjan; Orović, Irena; Sejdić, Ervin (Springer International Publishing : Imprint: Springer, 2016)
This book covers the basics of multimedia systems and signal processing. Emphasis is given to the analysis and processing of multimedia signals (audio, images, and video). Detailed insight into the most relevant mathematical apparatus and transformations used in multimedia signal processing is given. A unique relationship between different transformations is also included, opening new perspectives for defining novel transforms in specific applications. Special attention is dedicated to the compressive sensing area, which has a great potential to contribute to further improvement of modern multimedia systems. In addition to the theoretical concepts, various standard and more recently accepted algorithms for the reconstruction of different types of signals are considered. Finally, the book connects these principles to other important elements of multimedia systems, such as the analysis of optical media, digital watermarking, and telemedicine. This book is an ideal book for students, professionals, and researchers in the field of multimedia and related fields with a need to learn the fundamentals of multimedia systems and signal processing. New to this edition: Introduction of the generalization concept to consolidate the time-frequency signal analysis, wavelet transformation, and Hermite transformation Inclusion of prominent robust transformation theory used in the processing of noisy multimedia data as wel l as advanced multimedia data filtering approaches, including image filtering techniques for impulse noise environment Extended video compression algorithms Detailed coverage of compressive sensing in multimedia applications.